Injury Statistics - Schöffl, Volker; Lutter, Christoph; Jones, G. (Springer International Publishing, 2022)
Sports epidemiology is the study of the determinants and distribution of injury. The classification of climbing activity enables researchers to evaluate the risk of injury associated with a particular type of climbing behavior and to profile the risk of injury associated in engaging in different forms of climbing activity. For example, the inherent risk factors associated in alpine climbing are completely different to those encountered by indoor competition climbers. In outdoor rock climbing, most injuries are acute in nature and affect the lower extremities, usually due to a fall and impact with the climbing surface and/or the ground. For sport, indoor, and competition climbing, including bouldering, chronic overstrain injuries are common and most frequently affect the upper extremities. The UIAA Medical Commission’s scoring system is an established scale for grading injuries in climbing disciplines. The majority of reported injuries are of low-grade severity; however, fatal injuries still occur in all forms of climbing activity. Recently, an increase in more serious injuries has been reported predominantly occurring in modern indoor bouldering gyms.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Climbing injuries; Epidemiology; Injury grading; Injury incidence; Injury scores